FAKTOR PENYEBAB KORUPSI DANA DESA MERBAU KECAMATAN BUNUT KABUPATEN PELALAWAN TAHUN 2018 - Randi Wahyudi; Adlin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Corruption in funds at the village level is a serious problem that can hinder the development and development of the local community. This study aims to identify the factors causing financial corruption that occurred in Merbau Village, Bunut District in 2018. This research uses the theory put forward by Andi Hamzah (2005) which explains 4 points of factors that cause corruption. The research method used is qualitative research with a case study approach. Data were obtained through in-depth interviews with various related parties, such as village officials, community members and other related parties. In addition, data was also collected through direct observation in the field and analysis of related documents. The results of the study indicate that there are several factors causing financial corruption in Merbau Village. The corruption committed by the former Bunut village head with the initials EM was carried out for personal gain in fulfilling household needs. Corruption is also carried out in the form of buying goods for personal business. Low awareness of the importance of good financial governance. Many members of the village government do not understand the principles of accountability and transparency in managing village finances. Weak internal oversight and control. An ineffective monitoring system allows manipulation and misuse of village funds. Increasing community participation is also important, through counseling and active involvement in overseeing village finances. Keywords: Financial corruption, Merbau Village, Causative Factors, Financial Management, Village Fund.